Development of the Cijenuk Village Website to Enhance Community Participation and Public Information Accessibility - Deden Purnama Nugraha Putra; Ansori Ansori; Novi Widiastuti (Journal of Education and Teaching Learning, 2026)
This study aimed to develop the Cijenuk Village website as a community education medium to enhance community participation and public information transparency. The research employed a research and development approach using the ADDIE model, consisting of analysis, design, development, limited implementation, and evaluation stages. The research subjects included media experts, community education experts, and residents of Cijenuk Village as users. Data were collected through observation, interviews, and questionnaires, and analyzed using descriptive quantitative techniques with percentage feasibility analysis. The results indicated that the developed village website was categorized as highly feasible based on expert validation and received positive responses from community users. The website effectively improved public information accessibility and encouraged greater community participation in village development processes.